2021
DOI: 10.1093/pm/pnaa473
|View full text |Cite
|
Sign up to set email alerts
|

A Network Analysis of Clinical Variables in Chronic Pain: A Study from the Swedish Quality Registry for Pain Rehabilitation (SQRP)

Abstract: Background Efforts to identify specific variables that impact most on outcomes from interdisciplinary pain rehabilitation are challenged by the complexity of chronic pain. Methods to manage this complexity are needed. The purpose of the study was to determine the network structure entailed in a set of self-reported variables, examine change, and look at potential predictors of outcome, from a network perspective. Methods In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
0
22
1
Order By: Relevance
“…Due to the complexity of chronic pain, several variables influence the outcome of an interdisciplinary pain rehabilitation. A recent network analysis revealed acceptance, pain interference, anxiety, catastrophizing and depression as the most central variables in both pre-and post-treatment networks (Akerblom et al, 2021). A previous study demonstrated that the actual content of multidisciplinary pain centre clinical assessments, according to the ICF Low Back Pain Core set, provides multidisciplinary teams a universal language to support assessments across disciplines (Bagraith et al, 2018).…”
Section: Number Of Patients Selecting This Goal a Rank Bmentioning
confidence: 99%
“…Due to the complexity of chronic pain, several variables influence the outcome of an interdisciplinary pain rehabilitation. A recent network analysis revealed acceptance, pain interference, anxiety, catastrophizing and depression as the most central variables in both pre-and post-treatment networks (Akerblom et al, 2021). A previous study demonstrated that the actual content of multidisciplinary pain centre clinical assessments, according to the ICF Low Back Pain Core set, provides multidisciplinary teams a universal language to support assessments across disciplines (Bagraith et al, 2018).…”
Section: Number Of Patients Selecting This Goal a Rank Bmentioning
confidence: 99%
“…Hence, it is important to assess insomnia in patients with complex chronic pain. A network analysis (N = 2 241) reported that psychological variables, such as acceptance and depression mainly were associated with pain interference, whereas the associations with pain intensity and extent together with insomnia were weak [78]. These results taken together may be important for expectations about treatment results (i.e., improvements in psychological distress may not necessarily lead to important improvements in pain intensity).…”
Section: Clinical Presentationsresults From Sqrpmentioning
confidence: 99%
“…Pain acceptance has been questioned as an outcome measure as it also possesses the features of a process measure and has been described as a moderator. A significant change in pain acceptance (CPAQ-8 short form) with medium effect size was however seen in association with other pain outcome measures in a network analysis, indicating that acceptance may be directly affected by rehabilitation and hence constitute an outcome measure by itself [57].…”
Section: Principal Findingsmentioning
confidence: 90%